2020
DOI: 10.17230//ecos.2020.50.2
|View full text |Cite
|
Sign up to set email alerts
|

Are the effects of market concentration and income diversification on banking performance persistent?

Abstract: We analyze the effects of market concentration and income diversification on banking performance. We used a sample of 134 countries for the period 1994-2011 and used the GMM estimator proposed by Arellano and Bover (1995). Our results show that market concentration and income diversification have a positive and non-linear effect on bank performance. The non-linearity suggests that the positive effect is reversed if the banking industry has high levels of market concentration and income diversification. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Paltrinieri, et al (2021) not found some relationship between income diversification and stability for both conventional and Islamic banks. Finally, Muñoz, et al (2020) showed that income diversification had a positive and non-linear effect on the banks´ performance. The non-linear link suggests that the positive effect is reversed if the banking industry is highly diversified.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
See 2 more Smart Citations
“…Paltrinieri, et al (2021) not found some relationship between income diversification and stability for both conventional and Islamic banks. Finally, Muñoz, et al (2020) showed that income diversification had a positive and non-linear effect on the banks´ performance. The non-linear link suggests that the positive effect is reversed if the banking industry is highly diversified.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…To stablish if the assets, liabilities, and / or income diversification distresses or benefits Mexican banks on its profitability and /or risk, we partially replicated the methodological footsteps of Muñoz, et al (2020). Their mentioned research analysis showed that diversification has a positive and nonlinear effect on bank performance.…”
Section: Study Hypothesismentioning
confidence: 98%
See 1 more Smart Citation
“…The financial intermediation theory was initiated from the exertion of Mendoza, Yelpo, Velso Ramos and Fuentealba (2020). Financial intermediation is a procedure that comprises additional units putting coffers with monetary institutions who then lend to shortfall units, (Bandyopadhyay, 2021).…”
Section: Financial Intermediation Theorymentioning
confidence: 99%